Characterization and Exploration of Lignite for the Adsorption of lead(II) Ions - Jafar Ahamed, A.; Balasubramanian, N. (Asian Journal of Chemistry, 2010)
The adsorbent lignite was subjected to proximate analysis and the various parameters were reported. It was used for the successful adsorption of lead(II) species from wastewaters.